AI and the future of skills, volume 1: capabilities and assessments - (:unkn) unknown (OECD Publishing, 2021)
“Artificial intelligence (AI) and robotics are major breakthrough technologies that are transforming the economy and society. The OECD’s Artificial Intelligence and the Future of Skills (AIFS) project is developing a programme to assess the capabilities of AI and robotics, and their impact on education and work. This volume reports on the first step of the project: identifying which capabilities to assess and which tests to use in the assessment. It builds on an online expert workshop that explored this question from the perspectives of both psychology and computer science. The volume consists of expert contributions that review skills taxonomies and tests in different domains of psychology, and efforts in computer science to assess AI and robotics. It provides extensive discussion on the strengths and weaknesses of different approaches, and outlines directions for the project. The report can therefore be a resource for the research community of multiple fields and policy makers who wish to obtain deeper insight into the complexity of machine capabilities.” (editor; BIBB-Doku)
Keywords: L 6.2.1 Standards/Gütekriterien; 370; Künstliche Intelligenz; Roboter; Personalcomputer; Arbeitswelt; Bildungssystem; Kompetenz; Kompetenzentwicklung; Berufsbildung; Kompetenzfeststellung